Earthquakes associated subionospheric VLF anomalies recorded at two low latitude stations in the South Pacific region. (March 2022) - Kumar, Sarwan; Kumar, Sushil; Kumar, Abhikesh
Abstract: The JJI VLF (22.2 kHz) transmitter signal received at two low-latitude stations, one in Port Vila (geog. coord., 17.73°S, 168.33°E), Vanuatu and other in Suva (18.14°S, 178.44°E), Fiji, was analyzed for any VLF changes due to 16 Earthquakes (EQs) with magnitudes 5.5 to 7.7, during 2018 (JJI-Vanuatu path, 6.8 Mm) and 2007 to 2018 (JJI-Suva path, 7.5 Mm). The VLF signal amplitude analysis included terminator time (TT), average daytime and nighttime amplitude variation, nighttime fluctuation, and mother Morlet wavelet methods. Out of 16 EQs only eleven EQs have shown subionospheric VLF changes including the decrease in the amplitude for about 2–8 h on the EQ day, unusual shifts in the TT of up to 5–9 min, and the decrease in the average daytime and nighttime signal amplitude of about 1–1.5 dB and 1–5 dB, respectively, on the mainshock day of the EQs. The dA ( t ) < 0 condition was observed about 4–5 days before the EQ which stabilized after 3–4 days from the EQ day. A decrease in the non-normalized and normalized trend of below -2 σ (standard deviation) mark was found on the EQ day and an increase in the non-normalized and normalized NF and dispersion of above +2 σ mark on the day of seismic activity was found. Mother wavelet analysis of EQ associated changes in the signal amplitude showed a strong and enhanced presence of short frequency (∼0.05–0.10 mHz) wave-like signatures, a few days prior, on the day of EQ, and after the EQ day as compared to normal days. Highlights: Subionospheric VLF signal showed a pronounced decrease in the amplitude for about 2–8 h on the EQ day. The dA ( t ) < 0 condition was observed about 4–5 days before the EQ which stabilized after 3–4 days after the mainshock. Wavelet analysis of perturbed amplitude showed a presence of short frequency (∼0.05–0.10 mHz) wave-like signatures.